2007
DOI: 10.1097/meg.0b013e328011050f
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of Helicobacter pylori infection in young children in the Netherlands

Abstract: The prevalence of H. pylori infection in young infants in the general population in The Netherlands is low. Children with at least one non-Dutch parent form a risk group, however, for H. pylori infection in The Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
6
30
2
Order By: Relevance
“…[3][4][5] Similarly, it is well documented that H. pylori prevalence rates are falling in the developed world. [6][7][8][9][10][11] The prevalence of a condition affects test performance for given sensitivity and specificity values. To optimize test performance, disease prevalence should be incorporated in testing decisions, and sensitivity and specificity should be set locally, not globally.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Similarly, it is well documented that H. pylori prevalence rates are falling in the developed world. [6][7][8][9][10][11] The prevalence of a condition affects test performance for given sensitivity and specificity values. To optimize test performance, disease prevalence should be incorporated in testing decisions, and sensitivity and specificity should be set locally, not globally.…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter infections in children are acquired early in life, mainly via oral–fecal contact. In the Netherlands, the prevalence of H. pylori in children is very low (1.2%); most infected children are offspring of non-Dutch parents like our patient [13]. Our patient had a double infection, which may be coincidental but could also be based on his Iranian background.…”
Section: Discussionmentioning
confidence: 78%
“…Hp has evolved numerous strategies to enable its survival and persistence within the gastric mucosa including Several studies have shown that the prevalence of Hp infection is decreasing in adults and children in many countries [16,17]. This is attributed to improvement in socioeconomic status (number of family members per household, siblings sharing a bed, bathing facilities) and possibly antibiotic use.…”
Section: Introductionmentioning
confidence: 99%